Analisis Teks Qiro’ah dalam Kitab Al Arobiyah Lin Naasiin Jilid 2 dalam Efektifitas Pembelajaran - Nur Halim (PALAPA, 2020)
The qiroah text in al'arabiyah lin nasiin is very interesting to analyze because the book was compiled by asatidz native Arabic speakers for Indonesia. The ustadz deliberately compile textbooks as well as compile a guidebook for ustadz (the book lil mu'allim), the asatidz besides as a teacher as well as a person who jumped directly in the field. The author wants to know the extent of the form of qiroah text in the book "al arabiyah lin nasiin", whether each subject is really suitable for non-Arabic students, especially students from Indonesia. This research is a literature study, the focus of discussion is the text of Qiroah. The author gets the original arab tarkib and dhou 'which are beautiful because the original Arabic composer. This book is composed by presenting four lughawiyah maharah (istima ’, kalam, qira’ah, kitabah) and also presents Arabic tsaqofah and Islamic thaqofah. thaqafiyah competence about Islamic Arabic culture, and the next is ittishaliyah competence, namely the ability to communicate both verbally and in writing in various contexts. In addition, researchers found a method that is suitable for the conditions of students in Indonesia. Wa akhiron the authors provide conclusions and suggestions as an addition to improve the teaching of Arabic, especially in Qiroah lessons on the maharah side of kalam.